A historical study of Olympic water polo and the most prominent results of the winning participating teams of the men's group for the period 1900-2024 (Al-Muthanna Journal of Sport Education Sciences, 2026)
Water sports are one of the most difficult and beautiful sports activities because they take place in a water medium and require great muscle strength, some of which are individual games that depend on one player and some of them are teams The result depends on the play of the whole team Research Objective Identify the most prominent results of the winning participating teams of the men's group for the period 1900-2024 This study depends on the descriptive-analytical method, as are the most important conclusions The dominance of countries in the Olympic water polo game has not been static, but has changed with changing political and economic conditions. Britain dominated in the early 20th century, power shifted to Hungary after World War II, and Serbia and Croatia finally emerged as dominant powers in the 21st century, reflecting the influence of government subsidies, sports planning, and national identity in the evolution of the game. The most important recommendations are  the need to develop sustainable training and funding programs that focus specifically on developing countries or those that lack a strong history in water polo